THE EFFECT OF LONG EXPOSURE OF UV RADIATION ON ERYTHEMA AND MELANIN INDEX - Isnaini Isnaini; Ika Kustiyah Oktaviyanti; Eko Suhartono (Berkala Kedokteran, 2022)
UV radiation are divided into 3, namely UV A (400 – 315 nm), UV B (315-280 nm), UV C (280 – 100 nm). UV C radiation have the greatest effect on skin damage compared to UV A and UV B. UV radiation can reach the earth's surface, that can cause burning of the skin with signs such as redness of the skin (erythema), pain, blistering and peeling of the skin. Until now there has been no research on the effect of long exposure of UV C radiation on the erythema and melanin index, so aim this research is know about the effect of long exposure of UV C radiation on the erythema and melanine index. This research was conducted by giving exposure to rat that had been shaved with variations in exposure time, namely 5 minutes, 10 minutes, 15 minutes and 20 minutes. The skin that has been exposed with UV radiation will be photographed for color analysis using a chromometer. The results showed that exposure of UV radiation for 10 minutes caused the greatest increase in the melanin and erythema index